Narsisme Versus Rasa Hormat Dalam Beribadah (Sebuah Fenomena Generasi Z Dalam Memaknai Ibadah) - Melyda Rajagukguk; Hanna Dewi Aritonang; Haposan Silalahi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The aim of this research is to find out the meaning of worship that generation z feels in worship. This shows how important it is to respect God in worship, making God the center of worship. The meaning of worship can also be felt when we come to worship with the aim of establishing a relationship with God and others. The method used in this research is qualitative with a descriptive approach with 10 research subjects selected to collect data in the field. The results of the research show that Generation Z experiences a lack of meaning in worship and respect in worship when taking photos during worship activities, because it interferes with concentration when listening to God's word and during worship activities. Some opinions from generation Z say that the meaning of worship that they feel when taking photos of their worship activities is not reduced because they only take photos and concentrate again on attending the worship service, because they upload the photos after returning from worship. The purpose of generation z uploading photos of their worship activities on social media is to inform their social media friends that they are attending worship and also as one of generation z's discourses to remind and invite their social media friends to come to worship.